The dates of publication of L.A.G. Bosc’s Histoire naturelle des Crustacés - Low, Martyn E. Y. (Zootaxa, 2012)
The Histoire naturelle des Crustacés, contenant leur Description et leurs Moeurs; avec figures dessinées d’après nature by Louis Augustin Guillaume Bosc was published in two volumes in “An X” (Bosc 1801a, b; Fig. 1). The tenth year (“An X”) of the French Revolutionary calendar began on 23 September 1801 and ended on 22 September 1802 (Kerzhner 1984: 411). Sherborn (1922: xxviii) gave the dates of publications for both volumes of Bosc (1801a, b) as “1802”. Boyko (2008: 114) showed that Bosc’s (1801a, b) work was published prior to 28 April 1802, which was accepted by the International Commission on Zoological Nomenclature in Opinion 2238 (ICZN 2009: 371).